Information and Communication Technologies in Tourism 2018 Proceedings of the International Conference in Jönköping, Sweden, January 24-26, 2018 (Springer International Publishing, 2018)
This book presents the latest research into the application of information and communication technologies within the travel and tourism sectors. Readers will find insightful contributions on a wide range of topics, including digital marketing, social media and online travel reviews, mobile computing, augmented and virtual reality, gamification, recommender systems, electronic distribution, online education and learning, and the sharing economy. Particular attention is devoted to the actual and potential impact of big data, and the development and implementation of digital strategies, including digital marketing and the digital economy. In addition to the description of research advances and innovative concepts, a number of informative case studies are presented. The contents of the book are based on the 2018 ENTER eTourism conference, held in Jönköping, Sweden. The volume will appeal to all academics and practitioners with an interest in the most recent developments in eTourism. .